Superstar - Davis, Mandy (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2017)
Enrolling in public school after years of homeschooling, Lester, a mildly autistic fifth-grader, struggles to adapt and manage symptoms before becoming eager to win a science fair, discovering an unexpected truth along the way.
Keywords: Autism -- Fiction; Science fairs -- Fiction; Public schools -- Fiction; Schools -- Fiction; Autism -- Fiction; Science -- Exhibitions -- Fiction; Public schools -- Fiction; School stories